Sonographic and Doppler Sonographic Diagnosis of Necrotizing Enterocolitis in Preterm Infants and Newborns - Deeg, Karl Heinz (Ultraschall in der Medizin, 2019)
Necrotizing enterocolitis (NEC) occurs primarily in immature preterm infants with low birth weight. It has a prevalence of 7-11% with a poor prognosis and a mortality rate of 20-40%. Plain abdominal radiography is still considered the diagnostic method of first choice even though ultrasound can visualize significantly more findings suspicious for NEC. Such as thickened bowel walls, dilated fluid-filled bowel loops, and gas bubbles in the intestinal wall, portal vein. Moreover, it is possible to assess intestinal peristalsis, to differentiate between intraluminal and extraluminal fluid and to assess the location of fluid accumulations and their internal echo pattern. In addition, free intraabdominal gas can be visualized on ultrasound. Increased flow rates in the mesenteric arteries and decreased flow in the portal vein can be detected on Doppler ultrasound in NEC. Color-coded Doppler ultrasound can be used to differentiate between bowel loops with increased and decreased perfusion and thus at risk for perforation. Ultrasound is therefore superior to conventional radiography in many regards and should replace it as the diagnostic method of first choice not least because of its noninvasive nature.
CRIS-Team Scopus Importer:2019-06-25